Effect of spouse's participation in childbirth preparation classes in the promotion of social support among pregnant women: A field trial - Zeinab Soltanshahi; Nezal Azh; Mark D Griffiths; Fatemeh Ranjkesh (Wolters Kluwer Medknow Publications, 2020)
Introduction: The purpose of this study was to investigate the effect of spouse's participation in childbirth preparation classes in the promotion of social support among pregnant women. Methods: The present study was a field trial comprising 150 pregnant women who participated in the childbirth preparation classes of health centers in Alvin and Mohammadiehin Qazvin (Iran). Pregnant women were selected using the convenience sampling and were randomly divided into two groups (i.e. intervention and control groups using block allocation). The intervention group participated in eight sessions of childbirth preparation classes with their spouses. The control group participated in eight sessions of childbirth preparation classes based on the protocol developed by the Iran Ministry of Health. The Social Support Survey (SSS) was completed before and after the intervention. Data were analyzed using the descriptive and analytical statistics tests such as Mann-Whitney and Friedman's through the SPSS software version 24. P < 0.05 was considered statistically significant. Results: The mean score on the SSS before sessions in the intervention and control group was 60.65 (standard deviation [SD] ± 6.69) and 61.63 (SD ± 4.97), respectively (P < 0.05). After sessions, the mean score of social support statistically significantly increased in the intervention group as compared to the control group (83.31 [SD ± 8.91] vs. 60.65 [SD ± 0.80]; P < 0.001). Conclusion: The results suggest that the presence of spouses in preparation classes for childbirth along with modified content of the sessions promotes social support among pregnant women. Based on these findings, participation in parental training for childbirth is recommended for couples.